2001
DOI: 10.1088/0264-9381/18/23/323
|View full text |Cite
|
Sign up to set email alerts
|

Null cone preserving maps, causal tensors and algebraic Rainich theory

Abstract: A rank-n tensor on a Lorentzian manifold whose contraction with n arbitrary causal future directed vectors is non-negative is said to have the dominant property. These tensors, up to sign, are called causal tensors, and we determine their general mathematical properties in arbitrary dimension N . Then, we prove that rank-2 tensors which map the null cone on itself are causal tensors. Previously it has been shown that, to any tensor field A on a Lorentzian manifold there is a corresponding "superenergy" tensor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(155 citation statements)
references
References 32 publications
2
153
0
Order By: Relevance
“…In [3] it was shown in arbitrary dimension that a symmetric tensor T ab which satisfies the dominant energy condition can be written as the superenergy tensor of a simple p-form [8], T ab = 4 g ab T cd T cd . That a p-form is simple means that it is a wedge product of p 1-forms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [3] it was shown in arbitrary dimension that a symmetric tensor T ab which satisfies the dominant energy condition can be written as the superenergy tensor of a simple p-form [8], T ab = 4 g ab T cd T cd . That a p-form is simple means that it is a wedge product of p 1-forms.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the dominant energy condition could be removed since T ac T b c = 1 4 g ab T cd T cd implies that either T ab or −T ab satisfies the dominant energy condition. Therefore the conclusion without the dominant energy condition is ±T ab = In [2] superenergy tensors of more general p-forms were considered and the results of [3] were generalized in the way that the condition T ac T b c = 1 4 g ab T cd T cd was replaced by a third-order equation for T ab .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore we can even extend it to higher rank tensors by means of the following definition [49,10] Definition A.1 A tensor T ∈ T 0 r (x) is said to be future (respectively past) if T( u 1 , . .…”
Section: Discussionmentioning
confidence: 99%
“…By the way, it is also known that any of the following conditions is equivalent to items 1, 2 (this yields bounds on the possible curvatures): (a) ∃a In fact, any of these items implies item 2, by using that any lightlike vector can be approximated by both, timelike and spacelike ones. For some algebraic extensions to higher order tensors, see [3].…”
Section: Proposition 23 a Lorentzian Manifold Is Time-orientable Ifmentioning
confidence: 99%